Anthropogenic Geomorphological Mapping of the Central Sector of the João Pessoa Metropolitan Region (PB), Brazil - Barbosa, Tamires Silva; Furrier, Max (Revista Brasileira de Geomorfologia, 2023)
This work presents and discusses the application of a new geomorphological mapping methodology focusing on anthropogenic landforms. The study area is the central sector of the metropolitan region of Joao Pessoa (state of Paraíba, Northeast Brazil), where there are densely urbanized areas and rural areas with high human intervention. The proposed geomorphological mapping methodology was developed based on Brazilian, English and Italian experiences and included extensive fieldwork. The final map elaborated covers from morphostructures to current anthropogenic landforms, proposing a broad and integrated legend representing all mapped taxa. The geomorphological map produced, in addition to being a synthesis of the geomorphological research developed, presents itself as an important tool for urban and environmental planning.